Polish printing vocabulary of the turn of the 19th and 20th centuries. Research postulates - Jarosz, Beata (Papers in Linguistics, 2021)
The article discusses professional printing vocabulary in use at the turn of the 19th and 20th centuries, which has not been subject to linguistic description so far. The author demonstrates the validity of undertaking research into this segment of the Polish lexicon, defines aims and tasks of the research, and cites numerous publications (specialist textbooks, guides, and periodicals) that are valuable sources of empirical material. Moreover, she indicates sample words that were included in old-time specialist lexicons (e.g. kolumna ‘page’) and in contemporary general Polish language dictionaries (e.g. korekta ‘proofreading’), which confirms those expressions’ broad circulation and attests to the stability of the printing nomenclature. The author also emphasizes the necessity of verifying existing theories, supplementing lexicographical data (e.g. taking into account feminine forms of nouns like linotypistka ‘a woman who works on a linotype machine’) and creating a specialist lexicon and corpus of texts about printing.